It is possible to maintain productivity and quality standards in carnation with less nitrogen in the fertigation formula - Baracaldo, Adriana del Pilar; Flórez, Víctor J.; González, Carlos A. (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Although nitrogen is the most widely used fertilizer in agriculture, it contaminates the surface and groundwater through leaching. A decrease in the concentration of total nitrogen and changes in the ammonium:nitrate ratio can provide information for a better use of this nutrient. The objective of this study was to evaluate the effect of a decrease in total nitrogen and an increase in the percentage of N-NH4+ on indicators of growth, productivity, quality and nitrogen use efficiency (NUE) in carnation cultivation. In the Centro Agropecuario Marengo at the Universidad Nacional de Colombia, two concentrations of total nitrogen were evaluated (200-140 mg L-1 in the vegetative phase and 160-112 mg L-1 in the productive phase) with three ratios of N-NH4:N-NO3 (5:95, 15:85 and 25:75) in standard carnation plants cv. Don Pedro grown in substrate. In both fertigation formulas, similar productivity and qualities were obtained, and the formula with less total N provided better NUE, mitigating the negative impact of this nutrient on the environment. Likewise, the ammoniacal component played a preponderant role: the number of floral stems per plant decreased as the ammoniacal component increased, similar to that observed with the percentage of flowering stems in the ‘Select’ quality grade.